Food Labels, Genetic Information, and the Right Not to Know - Loi, Michele (Kennedy Institute of Ethics journal, 2014)
, Many people believe that individuals have a right not to know their genetic disease risk. Here it is argued that, if this is correct, individuals also have a right not to know their diet-related disease risk. Reasons to remain ignorant are analogous in the case of risk related to diet and genetic susceptibilities. It follows that any policy to promote healthy diets (e.g. through “judgmental” food labels, such as traffic light labels, or, hypothetically, scary pictures similar to those found in cigarette packets) ought to protect the individual right not to know.